Foxes caught in the same snare: a methodological review of social radon studies. Issue 3 (4th March 2023) - Muric, Melisa; Thijssen, Peter; Turcanu, Catrinel; Perko, Tanja; Tomkiv, Yevgeniya
Abstract: Mitigating risk from exposures to indoor radon is a critical public health problem confronting many countries worldwide. In order to ensure effective radon risk management based on social scientific evidence, it is essential to reduce scientific uncertainty about the state of social methodology. This paper presents a review of methodological (best) practices, and sensitivity to bias, in research on public attitudes and behaviours with regards to radon risks. Using content analysis, we examined characteristics of research design, construct measurement, and data analysis. Having identified certain challenges based on established and new typologies used to assess methodological quality, our research suggests that there is a need for attention to (limitations of) cross-sectional design, representative and appropriate sampling, and a pluralist approach to methods and analysis. Furthermore, we advocate for more comparative research, rigorous measurement and construct validation. Lastly, we argue that research should focus on behavioural outcomes to ensure effective radon risk management. We conclude that for any field to thrive it is crucial that there is methodological reflexivity among researchers. Our recommendations serve as a useful guide for researchers and practitioners seeking to understand and enhance the rigor of social methodology in their field.